TUHAN, MANUSIA DAN ALAM PERSPEKTIF PENDIDIKAN ISLAM - Mukani Mukani (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Humans have some excesses that other creatures do not have. By the excesses, humans try to understand and comprehend the messages from God through holly book (qauliyyah) or phenomena of the universe (kauniyyah). The involvement of humans in education is something that can not be avoided, because humans have importance to conserve and bequeath the values of their communities to the next generation and to transform the knowledge they have gotten and created. Related to the universe, the next education has to be able to admit the influence of the universe existence to the education it self. The universe must become framework or mindset in education. The universe is the right way to admit humans’ boundary in implementing their function as khalifah or servant of God. By introspecting to the universe, educated humans will not have negative characteristics because the universe has many verses of kauniyyah for humans. The universe is subject and also object in education that must be re-accommodated the existence. Not only looking at the universe from tight paradigm by watching closely the technically phenomena but also as the great cosmos covers and influences humans life.